Cumplimiento del protocolo score mama clave azul en mujeres embarazadas con preeclampsia en el Hospital Básico de Baba del Cantón Baba periodo octubre 2019 – marzo 2020. - Guambo Aimara, Sebastian Noe (2020)
Maternal and neonatal mortality are indicators that translate the degree of development and guarantee of rights in society. When a woman dies, she compromises the development of children and the family. It is important to know how compliance with the Blue Key Mom Score Protocol influences the pregnancy of women with preeclampsia at the Basic Hospital of Baba, so that the objective was to determine how compliance with the Blue Key Mom Score Protocol influences pregnancy of women with preeclampsia at the Baba Basic Hospital of the Baba canton, the methodology proposed was a descriptive investigation with quantitative modality that allows the achievement of the objectives set, the results obtained were that there is no optimal application in the key breast score protocol blue since there are marked deficiencies in some parameters such as the taking of temperature, the measurement of urine excreta, taking of proteinuria which are essential for the actual calculation of the breast score and, in conclusion, compliance with the Blue Key Mom Score Protocol directly influences the pregnancy of women with preeclampsia in view of and the strict application of the same will contribute to the improvement of the patient's health by providing well-being to the mother-child binomial on the other hand, the omission of the application of the partial blue key breast score protocol could partially or totally trigger the development of eclampsia and the worst of cases maternal death.